Child Custody Due to Divorce in a Mixed Marriage (Study of Decision Number 73/PDT.G/2019/PN BTL JO. Decision Number 96/PDT/ 2020/PT YYK) - Haura, Nayzalika Dzikra; Heriyani, Endang (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Mixed marriage refers to a marriage involving couples with different nationalities, with one party being an Indonesian citizen. Such marriages frequently occur in various countries due to work activities or tourism. One of the issues arising from mixed marriages is divorce, which has implications for the children born from these marriages, especially regarding their custody, as they are often unable to choose whether to live with their mother or father following the divorce. Typically, both parents desire custody, resulting in legal disputes brought before the court. In such cases, the judge's considerations are crucial, as they must examine and decide the case by prioritizing the best interests of the child to ensure the fulfillment of their rights and development. This research explains the judge’s considerations in determining child custody resulting from divorce in mixed marriages. This research is normative juridical research, utilizing secondary data derived from primary and secondary legal materials. Based on the analysis, it is concluded that in determining child custody due to divorce in mixed marriages, the judge may grant custody rights to both parents. In this case, the mother, an Indonesian citizen, was granted custody of the first child, who was nine years old, based on the panel of judges considering the child’s preference, who felt more affectionate towards his mother and practiced Catholic prayers with her in daily life. Meanwhile, the father, a foreign national, was granted custody of the second child, who was five years old, because the child expressed affection towards his father and stepmother, Mama Lena, and practiced Islam in his daily prayers, following his father’s religion. Therefore, the panel of judges based the determination of child custody on the child's preferences to ensure their best interests.